Probiotic Lactobacillus paracasei IMPC 2.1 strain delivered by ready-to-eat swordfish fillets colonizes the human gut after alternate-day supplementation. (August 2015) - Valerio, F.; Lonigro, S.L.; Giribaldi, M.; Di Biase, M.; De Bellis, P.; Cavallarin, L.; Lavermicocca, P.
Highlights: Swordfish fillets sustain viable population of a probiotic Lactobacillus paracasei . The strain does not affect protein profile and total free aminoacid content of fish. Ready to eat fillets deliver the probiotic L. paracasei IMPC 2.1 into the human gut. L. paracasei IMPC 2.1 colonizes the human gut in an alternate-day-based pilot study. Probiotic intake is effective in increasing genetic diversity of faecal LAB. Abstract: Ready-to-eat (RTE) swordfish fillets were used in a human feeding study involving 8 volunteers to assess the suitability of the fish matrix in delivering viable cells of the probiotic Lactobacillus paracasei IMPC 2.1. The strain did not affect the protein profile and total free amino acid content along the fillet shelf life. Volunteers consumed 100 g of probiotic RTE portion delivering 9 log CFU of bacterial cells, on alternate days over 20 days. Five subjects resulted to be colonized by the probiotic strain, at levels ranging from 6.30 to 7.74 log CFU/g of faeces, after eating 5 portions of the product (T1, 10 days). After 20 days (T2, 10 portions) the probiotic strain was recovered in the faeces of all subjects at concentrations ranging from 6.15 to 7.47 log CFU/g. This study demonstrated that 5 portions of probiotic RTE fish fillets consumed on alternate days allowed the transient colonization of gut by L. paracasei IMPC 2.1.